CREATIVE BUSINESS INNOVATION ANALYZING THE GIG ECONOMY’S IMPACT ON THE LIVELIHOODS OF CREATIVE-PRENEURS IN SOUTHEAST ASIA - Pong Krit; Marcus Tan; Rachel Chan (Yayasan Adra Karima Hubbi, 2026)
This study investigates the impact of the gig economy on the livelihoods of creative-preneurs in Southeast Asia, with a focus on income stability, creative autonomy, and business sustainability. The research aims to analyze both the opportunities and structural challenges faced by creative-preneurs operating through digital platforms. A mixed-methods approach was employed, combining a quantitative survey of 100 creative-preneurs across multiple Southeast Asian countries with in-depth semi-structured interviews involving 20 selected participants. Quantitative data were analyzed using statistical correlation and regression techniques, while qualitative data were examined through thematic analysis. The findings reveal that while 72% of respondents experience significant income fluctuations and 65% report decreased job security, a majority benefit from increased creative autonomy and business growth. A significant positive relationship was found between creative autonomy and business expansion, whereas income instability negatively affected job satisfaction and career sustainability. The novelty of this research lies in its sector-specific and regional focus, addressing a gap in existing gig economy studies that largely overlook creative industries in Southeast Asia. The implications of this study extend beyond socio-economic analysis, contributing conceptually to physics-related modeling of complex systems and uncertainty, as well as to physics education by offering real-world contextual applications for data analysis, system dynamics, and interdisciplinary problem-solving within STEM-based learning frameworks.